Live imaging and gene expression analysis in zebrafish identifies a link between neutrophils and epithelial to mesenchymal transition. - Christina M Freisinger; Anna Huttenlocher (PLoS ONE, 2014)
Chronic inflammation is associated with epithelial to mesenchymal transition (EMT) and cancer progression however the relationship between inflammation and EMT remains unclear. Here, we have exploited zebrafish to visualize and quantify the earliest events during epithelial cell transformation induced by oncogenic HRas(V12). Live imaging revealed that expression of HRas(V12) in the epidermis results in EMT and chronic neutrophil and macrophage infiltration. We have developed an in vivo system to probe and quantify gene expression changes specifically in transformed cells from chimeric zebrafish expressing oncogenic HRas(V12) using translating ribosomal affinity purification (TRAP). We found that the expression of genes associated with EMT, including slug, vimentin and mmp9, are enriched in HRas(V12) transformed epithelial cells and that this enrichment requires the presence of neutrophils. An early signal induced by HRas(V12) in epithelial cells is the expression of il-8 (cxcl8) and we found that the chemokine receptor, Cxcr2, mediates neutrophil but not macrophage recruitment to the transformed cells. Surprisingly, we also found a cell autonomous role for Cxcr2 signaling in transformed cells for both neutrophil recruitment and EMT related gene expression associated with Ras transformation. Taken together, these findings implicate both autocrine and paracrine signaling through Cxcr2 in the regulation of inflammation and gene expression in transformed epithelial cells.